Identification of discrete phase objects from digital images - Teng, Woan Wee. (2010)
Digital image processing and analysis is a technique commonly used to study the size distribution of the discrete phase objects in a multiphase flow system. Size distribution of the discrete objects such as particles, bubbles and droplets in multiphase flow systems is of high importance. The first step in the size measurement of an object from the captured digital image is to identify the object accurately from the image. A method is proposed to identify discrete phase object from digital images using the concept of region segmentation and histogram analysis. Some of the crucial steps are evaluated by simulation while others are considered theoretically. The proposed method has high potential to be used for object identification from digital images.